P793 Risk factors for incident non-gonococcal urethritis (NGU) in men who have sex with women (MSW) attending an STD clinic. (14th July 2019) - Rowlinson, Emily; Chambers, Laura; Lowens, Sylvan; Morgan, Jennifer; Robinson, Tashina; Romano, Sarah; Leipertz, Gina; Golden, Matthew; Hughes, James; Manhart, Lisa
Abstract : Background: Incidence and risk factors for NGU remain poorly defined. We conducted a cohort study to estimate incidence and identify associated risk factors in MSW. Methods: We enrolled cisgender male STD clinic patients age ≥16, who reported exclusively female partners. At enrollment and six monthly follow-up visits, men underwent a clinical exam, provided urethral swab and urine specimens, and completed a sexual behavior survey. We tested for chlamydia (CT) and Mycoplasma genitalium (MG) using Aptima. NGU was defined as urethral symptoms or visible discharge plus ≥5 polymorphonuclear leukocytes per high-power field on a Gram-stained slide. NGU following an NGU-negative visit was considered incident. We estimated incidence of NGU overall, pathogen-associated (MG or CT) and idiopathic NGU using Poisson regression for clustered outcomes. We performed relative risk binomial regression for clustered data to identify characteristics associated with incident NGU. Results: From 08/2014-08/2018, 254 participants had ≥1 follow-up visit, contributing 100.6 person-years at risk during follow-up. Median age was 32 (range=17–71), 53% were white and 24% black. Eighty-four (33%) had NGU at enrollment. Forty-five men had 53 cases of incident NGU (incidence=0.53 per person-year (95% confidence interval [CI]=0.39–0.71)). Incidence of pathogen-associated and idiopathic NGU was 0.06 (95% CI 0.03–0.13) and 0.47 (95%CI = 0.34–0.63), respectively. After adjustment for age, condom use and new partners during follow-up, risk of incident NGU was higher among black men (adjusted RR (ARR)=2.2; 95%CI=1.1–4.4), those with a history of NGU before enrollment (ARR=3.1; 1.5–6.5) and more sex partners during follow-up (ARR=1.2 per partner; 1.0–1.5); risk was lower among men who used lubricant at last sex (ARR=0.44; 0.20–0.96). Conclusion: Incidence of NGU was high, predominantly idiopathic, and associated with traditional socio-behavioral characteristics, but not age, condom use, or new partners. The lubricant-use association was unexpected and warrants further exploration. More precise daily diary data may yield additional insights. Disclosure: No significant relationships.